2019
DOI: 10.1007/s41669-018-0115-y
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Avelumab for Metastatic Merkel Cell Carcinoma

Abstract: Background Metastatic Merkel cell carcinoma (mMCC) is a rare and aggressive skin cancer. Until recently, there were no licensed treatment options for patients with mMCC, and prognosis was poor. A cost-effectiveness analysis was conducted for avelumab, a newly available treatment option for mMCC, versus standard care (SC), from a UK National Health Service perspective. Methods A partitioned survival model was developed to assess the lifetime costs and effects of avelumab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…The importance of appropriate survival extrapolation is particularly highlighted within the context of HTA, as noted within NICE TSD 14: "different methods have varying functional forms and are likely to result in different survival estimates, with the differences potentially largeparticularly when a substantial amount of extrapolation is required" [9]. A model under-estimating RMST by approximately 1 month would translate to an under-estimate in life-years gained of 0.08, equivalent to approximately 0.06 (undiscounted) QALYs (assuming a utility value of 0.71 per the published cost-utility analysis of avelumab in mMCC) [43]. Though a seemingly small decrease in QALYs gained, were this decrement applied to the published base-case cost-utility results, the incremental cost-effectiveness ratio (ICER) would increase by approximately £1000.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of appropriate survival extrapolation is particularly highlighted within the context of HTA, as noted within NICE TSD 14: "different methods have varying functional forms and are likely to result in different survival estimates, with the differences potentially largeparticularly when a substantial amount of extrapolation is required" [9]. A model under-estimating RMST by approximately 1 month would translate to an under-estimate in life-years gained of 0.08, equivalent to approximately 0.06 (undiscounted) QALYs (assuming a utility value of 0.71 per the published cost-utility analysis of avelumab in mMCC) [43]. Though a seemingly small decrease in QALYs gained, were this decrement applied to the published base-case cost-utility results, the incremental cost-effectiveness ratio (ICER) would increase by approximately £1000.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that avelumab is likely to be a cost-effective treatment option for UK patients with mMCC. 29 To fully assess ICI value in mMCC, additional factors such as clinical efficacy measures, safety, and patient-reported outcomes must be considered. 30–32 Previously published studies examining the costs related to the use of ICIs in patients with mMCC are not fully comparable to the current study due to different study criteria 4 , 19 , 33 or different healthcare systems.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study compared avelumab with chemotherapy, standard care, and best supportive care for UK metastatic merkel cell carcinoma (mMCC) patients and found out that avelumub was cost-effective as the WTP threshold of £50,000 per QALY (Bullement et al, 2019). There are some reasons why a different conclusion was provided.…”
Section: Discussionmentioning
confidence: 99%